Global burden of early-onset gallbladder and biliary tract cancer from 1990 to 2021 - Jin Liu; Wei Fang; XiangYi He; XianTu Zhang; Hong Liu (BMC Gastroenterology)
Abstract Background Gallbladder and biliary tract cancer (GBTC) denotes a range of invasive tumors. Emerging evidence has revealed a rising trend in the incidence of early-onset GBTC (EOGBTC) patients, referring to individuals under the age of 50 years old. We conducted an epidemiological study to assess the disease burden of EOGBTC. Methods Data on EOGBTC from 1990 to 2021 were sourced from the Global Burden of Disease Study 2021. Average annual percentage changes (AAPCs) and age-standardized rates (ASRs) were calculated to assess overall trends in the burden of EOGBTC. Statistical models including decomposition analysis, health inequality analysis, and Nordpred were utilized in the research. Results The study indicated over 24,555 prevalent cases, 13,611 new cases, and roughly 8777 deaths of EOGBTC in 2021. The global ASR of incidence and prevalence displayed increased trends, while the ASR of mortality and disability-adjusted life years (DALYs) were downward trends. East Asia and South Asia represented the heaviest disease burdens. The disease burden is mainly concentrated in the middle, low-middle, and low SDI regions. Decomposition analysis revealed that the primary influence of disease burden was population growth. Health inequalities showed improvement. Nordpred model forecasted that by 2040, global EOGBTC incidence and prevalence may steadily increase, while the deaths and DALYs display a general downward trend. Conclusions The overall burden of EOGBTC continues to be considerable, especially in regions with middle, low-middle, and low SDI levels. These findings underscore the necessity for innovative healthcare strategies to alleviate the burden faced by EOGBTC globally.